Millealab as A Virtual Reality-based Learning Platform for Slow Learners Students - Nurliasari, Lusiana; Kurniawan, Erwin Hari; Muchyidin, M Syaichul (Jurnal Paedagogy, 2025)
This research aims to analyze the to find outÂ the response of using Millealab on the material comprehension of slow learners. This study used a qualitative approach with a case study method. The Â subjects in this study were slow learners grade 8 students at SMP Plus Rahmat Kediri, East Java. The instruments used in this research are observation, interview, and observation which were then analyzed inductively. The result show that virtual reality (VR) helps slow learners connect abstract concepts with real experieces, which supports their understanding. The findings have immportant implications in inclusive education, where VRÂ can improve the cognitive growth and academic understanding of slow learners students.